2021
DOI: 10.36423/pharmacoscript.v4i1.610
|View full text |Cite
|
Sign up to set email alerts
|

FORMULASI DAN UJI AKTIVITAS GEL KOMBINASI EKSTRAK ETANOL DAUN LIDAH BUAYA (Aloe vera) DAN DAUN KEMANGI (Ocinum sanctum L.) SEBAGAI ANTI JERAWAT TERHADAP BAKTERI Staphylococcus epidermidis

Abstract: Jerawat merupakan penyakit kulit yang disebabkan oleh bakteri antara lain yaitu bakteri Staphylococcus epidermidis. Lidah buaya (Aloe vera) dan daun kemangi (Ocinum sanctum L.) mengandung saponin, flavonoid, dan tanin yang mampu menghambat pertumbuhan bakteri sehingga memiliki daya antibakteri. Penelitian ini bertujuan untuk mengetahui tingkat efektivitas dari kombinasi ekstrak lidah buaya (Aloe vera) dan daun kemangi (Ocinum sanctum L.) dalam bentuk sediaan gel terhadap bakteri Staphylococcus epidermis. Metod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Yield becomes a measure of solvent capacity in extracting chemical content. The yield of EDLB in this study was lower than that resulted by a previous study (22.32% yield), although both used simplicia powder as an extraction material and 96% ethanol solvent (Yasir et al, 2021). Meanwhile, other study obtained a low yield (1.20%) when using fresh aloe vera and extracted with 96% ethanol , but other researchers obtained a yield of 12.28% because the extraction technique was different even though using fresh aloe vera (Martono & Suharyani, 2018).…”
Section: Simplicia Extractcontrasting
confidence: 75%
“…Yield becomes a measure of solvent capacity in extracting chemical content. The yield of EDLB in this study was lower than that resulted by a previous study (22.32% yield), although both used simplicia powder as an extraction material and 96% ethanol solvent (Yasir et al, 2021). Meanwhile, other study obtained a low yield (1.20%) when using fresh aloe vera and extracted with 96% ethanol , but other researchers obtained a yield of 12.28% because the extraction technique was different even though using fresh aloe vera (Martono & Suharyani, 2018).…”
Section: Simplicia Extractcontrasting
confidence: 75%
“…Another study by Royani et al (2022), that as an antibacterial plant, A.vera contains active substances such as saponins, tannins, and flavonoids. Phytochemical screening of Aloe vera extract using 96% ethanol solvent also showed that the sample contained active compounds, namely phenolic compounds, flavonoids, tannins, and saponins, and was negative for alkaloid compounds (Yasir et al, 2021).…”
Section: Content Of Active Compounds In Aloe Vera Extractmentioning
confidence: 99%
“…Menurut Zakaria (2022), Kombinasi ekstrak daun kemangi dan daun jeruk nipis mampu menurunkan laju pertumbuhan terhadap bakteri S. aureus. Kombinasi ekstrak lidah buaya dan daun kemangi memberikan efek kenaikan clear zone yang tercipta terhadap S. epidermidis dari 15 mm menjadi 16 mm (Yasir, 2021) Kedua tanaman terindikasi mengandung senyawa metabolit sekunder yang mempunyai daya antibakteri yang dibuktikan dalam penelitian-penelitian terdahulu sehingga menjadi dasar diperlukannya uji lanjutan mengenai kombinasi kedua ekstrak dalam menghambat pertumbuhan bakteri. Penelitian ini bertujuan untuk menguji aktivitas ekstrak kombinasi kulit alpukat dan daun kemangi serta ekstrak tunggal masing-masing.…”
Section: Pendahuluanunclassified